The presumption of labor. Legal anachronism or key piece for the recovery of the effectiveness of the labor law in Peru? - Sanguineti Raymond, Wilfredo (2007)
The «crisis of effectiveness» that now affects the Labor Law in Peru, constitutes the frame on which this work is done, the intention is to reflect on the utility of the denominated «presumption of labor relationship», institution of procedural nature directed to facilitate the proof of the existence of the contract of work in doubtful situations to surpass such state of things. For that reason we will consider the debate that this peculiar institution has subscribed from its origins to the present time and we will also pay special attention to the proposals that lately have put on the spotlight the possibility of its introduction within our legal ordering.